(untitled) (Research, Society and Development, 2024)
Objective: To evaluate the impact of Sleep Hygiene among elderly members of a primary health care unit in Recife, PE. Methodology: This was an evaluative, interventional, before-and-after study conducted from May to June 2024. Participants were elderly individuals aged 60 years or older, with preserved cognition, who attended the educational intervention. Data collection occurred at three points: sociodemographic questionnaire, sleep quality assessment using the Pittsburgh Sleep Quality Index (PSQI), and a second application of the PSQI 30 days after the first. Results: Fifteen elderly women participated, with an average age of 69.5 years; 73.3% were mixed-race or Black. Of the participants, 86.6% had children, and 80% lived with others. Additionally, 93.3% had comorbidities, such as hypertension and diabetes, and 33.3% used sleep medications. Before the educational intervention, 60% of the elderly participants had poor sleep quality, and 26.6% had sleep disorders. After 30 days, 46.6% of the participants showed improvements, including shorter time to fall asleep, fewer nighttime interruptions, and better perceived sleep quality. Conclusion: The study highlights that the elderly population faces sleep issues related to aging and sociobehavioral factors. Sleep hygiene proves to be effective in improving sleep quality among elderly individuals.